RECORD CENTER ARSIP SURAT KEPUTUSAN (SK) UNTUK UNIVERSITAS - Ni Wayan Wisswani; I Gusti Ngurah Bagus Catur Bawa; I Wayan Candra Winetra (Politeknik Negeri Batam, 2019)
Archive management for organizations is a necessity. ANRI recommends digital records archive management of evidence. University as one of the organizations also requires digitalization of archive management. In particular, management archives of decision letter documents (SK) are important documents that relate to the history of university activities. Digitalization of archive management helps address the weaknesses of managing damaged, lost and vulnerable manual archives and large management costs. Digitalization efforts are done by developing a computer based archive management application using PHP and MYSQL. This application manages university file archiving transactions centrally in order to keep activity history for decision making and as a shared storage media.